2019
DOI: 10.1109/jphot.2019.2902313
|View full text |Cite
|
Sign up to set email alerts
|

Highly Polarized Fluorescent Film Based on Aligned Quantum Rods by Contact Ink-Jet Printing Method

Abstract: In recent years, fluorescent quantum rods (QRs) receive much attention because of their properties of emitting specific wavelength polarized light with narrow full width at half maximum (FWHM). Therefore, QRs are usually aligned on devices, such as light emitting diodes, laser, and liquid crystal display (LCD), as a polarizer. In order to emit the light with a high degree of polarization (DOP), QRs need to be controlled and aligned almost along one direction on large-scaled devices. However, most of the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…9f (black)). 56 Meanwhile, as the etching progresses (Fig. 9f (red and blue)), the crystal shape of the etched samples (DR-3-2 and DR-3-4) gets degraded and the signal gradually decreases.…”
Section: Resultsmentioning
confidence: 97%
“…9f (black)). 56 Meanwhile, as the etching progresses (Fig. 9f (red and blue)), the crystal shape of the etched samples (DR-3-2 and DR-3-4) gets degraded and the signal gradually decreases.…”
Section: Resultsmentioning
confidence: 97%
“…14 Mechanical stretching to align NR films has a trade-off between degree of alignment and robustness of the films, with higher degrees of stretching (>500%) achieving greater ordering of the film, but also higher risk of ripping or damaging the polymer film. 14 Additional methods to align NR assemblies include ligand− ligand interactions, 89,148−150 micellar assembly, 151 inkjet printing, 20,152,153 block copolymer directed assembly, 154−156 liquid interface assembly, 112,142,157 antisolvent−solvent-driven assembly, 158 and photoinduced assembly. 17,159 These techniques have also achieved high degrees of ordering within NR films, reaching theoretical maxima in terms of optical anisotropy for aligned NRs.…”
Section: Self Assembly Of Nrs Into Oriented Thin Filmsmentioning
confidence: 99%
“…Additional methods to align NR assemblies include ligand–ligand interactions, , micellar assembly, inkjet printing, ,, block copolymer directed assembly, liquid interface assembly, ,, antisolvent–solvent-driven assembly, and photoinduced assembly. , These techniques have also achieved high degrees of ordering within NR films, reaching theoretical maxima in terms of optical anisotropy for aligned NRs. Each of these techniques has trade-offs in efficiency of alignment, reproducibility, and ease of commercial application depending on the final goal of NR alignment, whether it be, for example, reduced reabsorption or directional and switchable emission.…”
Section: Synthesis and Assembly Of Cd-chalcogenide Nrsmentioning
confidence: 99%
“…For example, Zhou et al demonstrated the application of contact inkjet printing to align CdSe/CdS core/shell heterostructures, which yields a highly polarized fluorescent film. [ 547 ] Kuykendall et al demonstrated the alloying of GaN with InN to form GaN/InGaN heterostructures for light‐emitting applications. [ 548 ] Such precise control of the NW heterostructure enables the integration of light‐emitting devices into individual NWs.…”
Section: Functional Materials For Ink‐based Am Of Wearable Devicesmentioning
confidence: 99%